A CRITICAL REVIEW OF THE POST-REFORM STUDENT MOVEMENT ESCALATION (1999-2024) IN THE PARADIGM OF KARL MARX'S CLASS THEORY - Maulana, Donny; Hariyono; Utami, Indah Wahyu Puji; Widiadi, Aditya Nugroho (Universitas Negeri Medan, 2025)
The student movement has always emerged as a disruptive force in every episode of the history of the Indonesian national movement. It often emerges as a response to a condition (problem and crisis). The pattern of the escalation of the student movement is certainly different in several contexts of events in Indonesia every era. This article will more specifically discuss the pattern and escalation of the student movement in the post-reform context. The author takes the periodization between 1999-2024 as the limit of analysis. This is because during this period, there were several major events and unique phenomena that occurred related to how the pattern of the re-establishment of the escalation of the student movement after the 1998 reformation. The author will also discuss the phenomenon of student movement escalation using a class perspective (Karl Marx). In the process of preparing this article, the author used the literature study research method (library research). Desk research limits research activities to library collections without the need for field research. There are several findings from the process of unraveling the direction and results achieved by the student movement in the post-1998 Reformation period that the author found including; the phenomenon of bourgeois activism, the failure of efforts to elaborate the structural basis by movement actors, the urgency to translate an empowered and sovereign student movement, to the need to form an organic movement node by involving cross-sectors to achieve a people's movement that is not exclusive. Through the following contribution, the author hopes that today's students will no longer lose their identity as academic elites as well as social control and value guardians.